Service life assessment of historical building envelopes constructed using different types of sandstone: a computational analysis based on experimental input data - Kočí, Václav; Maděra, Jiří; Fořt, Jan; Žumár, Jaromír; Pavlíková, Milena; Pavlík, Zbyšek; Černý, Robert (TheScientificWorldJournal, 2014)
Service life assessment of three historical building envelopes constructed using different types of sandstone is presented. At first, experimental measurements of material parameters of sandstones are performed to provide the necessary input data for a subsequent computational analysis. In the second step, the moisture and temperature fields across the studied envelopes are calculated for a representative period of time. The computations are performed using dynamic climatic data as the boundary conditions on the exterior side of building envelope. The climatic data for three characteristic localities are experimentally determined by the Czech Hydrometeorological Institute and contain hourly values of temperature, relative humidity, rainfalls, wind velocity and direction, and sun radiation. Using the measured durability properties of the analyzed sandstones and the calculated numbers of freeze/thaw cycles under different climatic conditions, the service life of the investigated building envelopes is assessed. The obtained results show that the climatic conditions can play a very significant role in the service life assessment of historical buildings, even in the conditions of such a small country as the Czech Republic. In addition, the investigations reveal the importance of the material characteristics of sandstones, in particular the hygric properties, on their service life in a structure.
Keywords: Mechanical Phenomena; konstrukční materiály; Humans; Models, Theoretical; mechanické jevy; lidé; teoretické modely; Construction Materials